IgY Antibodies Protect against Human Rotavirus Induced Diarrhea in the Neonatal Gnotobiotic Piglet Disease Model - Vega, Celina Guadalupe (2012)
Group A Rotaviruses are the most common cause of severe, dehydrating diarrhea in children worldwide. The aim of the present work was to evaluate protection against rotavirus (RV) diarrhea conferred by the prophylactic administration of specific IgY antibodies (Ab) to gnotobiotic piglets experimentally inoculated with virulent Wa G1P[8] human rotavirus (HRV). Chicken egg yolk IgY Ab generated from Wa HRV hyperimmunized hens specifically recognized (ELISA) and neutralized Wa HRV in vitro. Supplementation of the RV Ab free cow milk diet with Wa HRV-specific egg yolk IgY Ab at a final ELISA Ab titer of 4096 (virus neutralization ?VN- titer=256) for 9 days conferred full protection against Wa HRV associated diarrhea and significantly reduced virus shedding. This protection was dose-dependent. The oral administration of semi-purified passive IgY Abs from chickens did not affect the isotype profile of the pig Ab secreting cell (ASC) responses to Wa HRV infection, but it was associated with significantly fewer numbers of HRV?specific IgA ASC in the duodenum. We further analyzed the pigs´ immune responses to the passive IgY treatment. The oral administration of IgY Abs induced IgG Ab responses to chicken IgY in serum and local IgA and IgG Ab responses to IgY in the intestinal contents of neonatal piglets in a dose dependent manner. To our knowledge, this is the first study to show that IgY Abs administered orally as a milk supplement passively protect neonatal pigs against an enteric viral pathogen (HRV). Piglets are an animal model with a gastrointestinal physiology and an immune system that closely mimic human infants. This strategy can be scaled-up to inexpensively produce large amounts of polyclonal IgY Abs from egg yolks to be applied as a preventive and therapeutic passive Ab treatment to control RV diarrhea.